Understanding Low Volume Application Technology: An Emerging Technology in the Citrus Industry - Lukasz L. Stelinski; Michael E. Rogers; Jamie D. Burrow (EDIS, 2010)
This 2-page illustrated trifold brochure describes this new application technology that has raised questions and concerns within the citrus industry. Written by Lukasz Stelinski, Michael Rogers, and Jamie Burrow (Yates), and published by the UF Department of Entomology and Nematology, September 2009.